Efektivitas Penerapan Aplikasi Sistem Informasi Kearsipan Dinamis Terintegrasi Di Dinas Perpustakaan Dan Kearsipan Provinsi Sulawesi Tengah - Bajrei, Nurfadila Mahfud K.; Mufti, Muhammad Irfan; Erdiyansyah (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine the extent of the effectiveness of the Implementation of the Integrated Dynamic Archive Information System (SRIKANDI) Application at the Central Sulawesi Library and Archives Service. The theory used in this study is Duncan's theory in Richard M. Strees (1985) which says there are 3 indicators in effectiveness, namely Goal Achievement, Integration, and Adaptation. In this study, the method used is qualitative descriptive. Meanwhile, in this study there are 5 informants, namely employees from the Central Sulawesi Library and Archives Service.The results of this study show that the effectiveness of the Implementation of the Integrated Dynamic Archive Information System (SRIKANDI) Application at the Central Sulawesi Library and Archives Service has not been running optimally. Judging from several indicators, namely the achievement of goals, andthe nature of the implementation of the SRIKANDI application, there is still a mixture between the use of the SRIKANDI application and the use of paper (paperless) so that this application does not operate in accordance with its purpose, namely to improve the quality and accountability of archives and reduce the use of paper. From the aspect of integration, it has been running effectively where socialization/technical guidance has been carried out regularly and gradually, starting with the creation of accounts for SRIKANDI admins, in addition to that, assistance in the use of the SRIKANDI application is always carried out, aiming to directly guide archive managers and SRIKANDI admins. From the aspect of adaptation, judging from the facilities and infrastructure in the implementation of the SRIKANDI application in the Central Sulawesi Library and Archives Office, it is not enough because in terms of the WIFI network which is still lacking, because in accessing the SRIKANDI application, the factor needed in addition to the computer is a sufficient internet network.